Co-MOF / TiO2 heterojunction-based photocatalysis-PMS activation catalyst as well as preparation method and application thereof
By constructing Co-MOF/TiO2 heterojunction and combining with PMS activation technology, the problem of insufficient light absorption capacity of traditional TiO2 photocatalytic materials under visible light is solved, efficient degradation of organic pollutants such as BPA and improve photocatalytic performance and water adaptability.
Patent Information
- Application Number
- CN202411519088.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-10-29
AI Technical Summary
The traditional photocatalytic material TiO2 limits the light absorption capacity within the visible light range because of its wide band gap, resulting in insufficient photocatalytic performance and it is difficult to effectively degrade difficult-to-degrade organic pollutants such as bisphenol A (BPA).
By combining TiO2 nanosheets with porphyrin-based metal organic frame (MOF) materials, Co-MOF/TiO2 heterojunction is constructed, the spectral response range of the catalytic material is broadened, and the oxidation capacity is enhanced through PMS activation technology to form synergistic photocatalysis -PMS activation catalyst.
It significantly improves the degradation efficiency of organic pollutants such as BPA, improves photocatalytic performance, and shows stable and efficient catalytic degradation performance in complex water bodies.
Smart Images

Figure CN119386933A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of photocatalysis, and specifically relates to a photocatalytic-PMS activated catalyst based on Co-MOF / TiO2 heterojunction, and a preparation method and application thereof. Background Art
[0002] In recent years, water pollution caused by persistent micropollutants and the global energy crisis have become hot issues of common concern to the international community and the scientific community. Bisphenol A (BPA) is a harmful micropollutant widely used in the polymer industry. It has obvious endocrine disrupting properties and can have adverse effects on the human hormone system, leading to a series of health problems such as cancer and abnormal reproductive system. In addition, BPA has high stability in the environment and is difficult to degrade naturally. In the industrial production process, a large amount of BPA enters rivers, lakes and soil through wastewater discharge. Even at low concentrations, BPA can pose a potential threat to aquatic organisms and human health. Although traditional wastewater treatment methods such as biological treatment, adsorption, ozone and oxidation can remove pollutants to a certain extent, they still have shortcomings such as low efficiency and high cost in degrading organic pollutants such as BPA. Therefore, the development of more effective pollutant removal technology and the application of green energy have become a major demand in the current field of environmental protection.
[0003] Advanced Oxidation Processes (AOPs) have attracted widespread attention in recent years due to their ability to efficiently treat organic pollutants. AOPs use reactive oxygen species to degrade pollutants, and are particularly good at treating difficult-to-degrade organic pollutants. The application of semiconductor photocatalysts in AOPs can generate free radicals by absorbing light energy, thereby achieving efficient degradation of pollutants. For example, TiO2, as a commonly used photocatalytic material, is widely used in wastewater treatment due to its high chemical stability, low cost, and excellent redox properties. However, the wide band gap (3.2 eV) of TiO2 limits its light absorption ability in the visible light range, resulting in the rapid recombination of photogenerated carriers, which limits its catalytic efficiency. Therefore, TiO2 still faces great challenges in practical applications and needs further improvement.
[0004] In order to solve the problem of limited photocatalytic performance of TiO2, researchers have proposed a strategy to improve photocatalytic efficiency by constructing heterojunctions. Combining TiO2 with semiconductor materials with narrow band gaps can broaden its light absorption range and improve the separation efficiency of photogenerated electrons and holes. In recent years, metal-organic framework materials (MOFs) have gradually become an emerging photocatalytic material due to their adjustable structure, large specific surface area and good photoresponsiveness. Among them, porphyrin-based MOFs are ideal for combining with TiO2 to construct organic-inorganic photocatalysts because of their ability to effectively capture visible light and their excellent photoelectric properties. In addition, permonosulfate (PMS) activation technology produces sulfate radicals (SO4 •- ) has a high redox potential and is widely used in the removal of refractory organic pollutants. Therefore, combining PMS with photocatalysis and exploring their synergistic effect to improve catalytic degradation efficiency has become one of the current research hotspots.
[0005] At present, there is almost no research on the synergistic effect of PMS activation and photocatalysis. Exploring the synergistic catalytic mechanism between the two is of great significance for improving the application efficiency of AOPs technology. Therefore, this study constructed a hybrid material with synergistic photocatalysis-PMS activation function by coupling TiO2 nanosheets with porphyrin-based MOFs for the degradation of BPA pollutants in water. Experiments show that the hybrid material has a high photogenerated carrier separation efficiency under visible light, and the PMS activation process further enhances the oxidation ability of the material, significantly improving the degradation efficiency of BPA. Summary of the invention
[0006] The purpose of the present invention is to provide a photocatalytic-PMS activation catalyst based on Co-MOF / TiO2 heterojunction and its preparation method and application, which solves the technical problem of low catalytic efficiency of traditional photocatalytic materials. Due to the synergistic effect of the photocatalytic-PMS activation coupling system, the catalyst exhibits good photocatalytic degradation effect on BPA.
[0007] In order to achieve the above object, the present invention adopts the following technical scheme: A preparation method of a photocatalytic-PMS activated catalyst based on Co-MOF / TiO2 heterojunction, comprising the steps of adding TiO2 nanosheets into DMF, uniformly dispersing the catalyst by ultrasonication, adding Co-MOF, stirring for 6-18 h, collecting the precipitate by centrifugation, washing and drying the catalyst, wherein the Co-MOF accounts for 5-40% of the total mass of the Co-MOF and TiO2 nanosheets, washing with ethanol, washing for 3-6 times, drying at 30-80°C, and drying for 10-20 h.
[0008] Furthermore, the preparation process of Co-MOF is as follows: cobalt acetate tetrahydrate is dissolved in methanol to form solution A, porphyrin ligand is dissolved in chloroform to form solution B, solution A and solution B are mixed and reacted in a high-pressure reactor at 60-120°C for 12-36 hours, naturally cooled to room temperature, centrifuged, solids are collected, washed with ethanol and then dried, wherein the molar ratio of cobalt acetate tetrahydrate and porphyrin ligand is (2-10):1, the concentration of cobalt acetate in solution A is 20-30 mmol / L, the concentration of porphyrin ligand in solution B is 1-10 mmol / L, the ethanol washing times are 3-6 times, the drying temperature is 30-80°C, and the drying time is 10-20 h.
[0009] Furthermore, the preparation process of TiO2 nanosheets is as follows: hydrofluoric acid is added dropwise to tetraisopropyl titanate, stirred evenly, reacted in a high-pressure reactor at 160-220°C for 12-36 hours, cooled naturally to room temperature, centrifuged, solids collected, washed with ethanol and dried, wherein the volume ratio of hydrofluoric acid to tetraisopropyl titanate is 1: (8-9). The concentration of the hydrofluoric acid is 35-40 wt%; the number of ethanol washings is 3-6 times, the drying temperature is 30-80°C, and the drying time is 10-20 hours.
[0010] The photocatalytic-PMS activated catalyst based on Co-MOF / TiO2 heterojunction is prepared by the above preparation method.
[0011] The above-mentioned photocatalytic-PMS activated catalyst based on Co-MOF / TiO2 heterojunction is used in the photocatalytic degradation of bisphenol A. The photocatalytic-PMS activated catalyst based on Co-MOF / TiO2 heterojunction is added to a solution containing bisphenol A, and a 50W LED lamp is used as the light source. Under circulating water cooling, PMS (persulfate) is added to photocatalytically degrade bisphenol A.
[0012] Furthermore, the concentration of bisphenol A in the solution containing bisphenol A is 10-50 mg / L, based on the solution containing bisphenol A, the added amount of Co-MOF / TiO2 heterojunction composite photocatalyst is 0.1-0.3 g / L, and the added amount of PMS is 0.2-0.4 g / L.
[0013] Compared with the existing method, the present invention has the following beneficial effects: 1. The preparation method of the photocatalytic-PMS activated catalyst based on Co-MOF / TiO2 heterojunction provided by the present invention greatly improves the photocatalytic performance: The present invention constructs an efficient organic-inorganic hybrid photocatalyst by combining TiO2 nanosheets with porphyrin-based metal organic framework (MOF) materials. Although traditional TiO2 has high chemical stability and redox ability, its wide band gap (3.2 eV) limits the absorption range under visible light, resulting in insufficient photocatalytic performance. However, the present invention successfully broadens the spectral response range of the catalytic material by combining with porphyrin-based MOF, especially enhances the light absorption capacity in the visible light region. The organic ligand of the porphyrin-based MOF not only acts as a photosensitive antenna, which can efficiently capture visible light, but also promotes the separation of photogenerated electrons and holes, avoiding the rapid recombination of electrons and holes. This improvement in carrier separation efficiency enables the material to generate more reactive oxygen species (ROS) during the photocatalytic process, thereby significantly improving the degradation efficiency of organic pollutants such as bisphenol A (BPA).
[0014] 2. The photocatalytic-PMS activation catalyst based on the Co-MOF / TiO2 heterojunction provided by the present invention has a synergistic catalytic mechanism. Compared with the conventional single photocatalytic mechanism, the synergistic effect between the heterojunction composite photocatalysts greatly improves the generation of active species. The high redox potential of cobalt ions can effectively activate PMS into a strong oxidant. The excellent light absorption performance of the heterojunction composite catalyst can generate photogenerated electron-hole pairs under visible light irradiation. These photogenerated carriers can be effectively captured by the adsorbed PMS, thereby further promoting the activation process of PMS. The two mechanisms of PMS activation and photocatalysis work synergistically in the composite catalyst to produce a large number of strong oxidizing species, thereby achieving efficient removal of the difficult-to-degrade BPA pollutants.
[0015] 4. The photocatalytic-PMS activated catalyst based on Co-MOF / TiO2 heterojunction provided by the present invention has strong adaptability to complex water bodies: the hybrid material of the present invention exhibits stable and efficient catalytic degradation performance in a wider range of reaction systems, which makes it suitable for different types of water environments. The present invention has excellent performance in different reaction systems under neutral conditions through coordinated PMS activation and photocatalytic reaction. In addition, the present invention also has strong anti-interference ability for coexisting ions such as chloride ions, nitrate ions, etc. that may exist in water bodies, ensuring its wide applicability in actual water treatment, especially in complex sewage treatment environments, it can still maintain a high degradation efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1The crystal structure of Co-MOF: (a) the basic structural unit in Co-MOF; perspective view of the Co-MOF structure along the crystallographic c-axis: (b) local pore structure; (c) space filling diagram; (d) skeleton diagram (metal-metal connection); Figure 2 The band structures of the catalysts prepared in Examples 1-4 and Comparative Examples 1-2: (a) UV-vis DRS spectra, (b) calculated band gaps; Figure 3 The removal effects of the catalysts prepared in Examples 1-4 and Comparative Examples 1-2 on BPA under different systems; the degradation kinetics (a) and pseudo-first-order kinetic fitting (b) of the catalysts prepared in Examples 1-4 and Comparative Examples 1-2 on BPA under visible light; the degradation kinetics (c) and pseudo-first-order kinetic fitting (d) of the catalyst prepared in Example 3 on BPA under visible light and PMS conditions, experimental conditions: pH = 7; [PMS] = 1.2 mM; [catalyst] = 0.4 g / L; [BPA] = 10 mg / L; Figure 4 The effect of the catalyst of Example 3 on the BPA removal rate under different conditions: (a) The effect of various anions on the BPA removal rate. (b) The effect of BPA removal rate in ionized water, tap water, lake water, river water and simulated seawater. Experimental conditions: pH = 7; [PMS] = 1.2 mM; [Catalyst] = 0.4 g / L; [BPA] = 10 mg / L; Figure 5 The cyclic performance and cyclic stability of the catalyst prepared in Example 3 are as follows: (a) cyclic degradation experiment on BPA; (b) PXRD patterns before and after catalysis. DETAILED DESCRIPTION
[0017] In order to better understand the present invention, the present invention is further described below by way of examples. The examples are only used to explain the present invention and do not constitute any limitation to the present invention.
[0018] The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention. Unless otherwise specified, the technical means used in the examples are conventional means well known to those skilled in the art, and the raw materials used are all commercially available products.
[0019] 5,10,15,20-Tetrakis(4-pyridyl)porphyrin (porphyrin ligand) (Zhengzhou Alpha Chemical Co., Ltd.), cobalt acetate tetrahydrate (Shanghai McLean Biochemical Technology Co., Ltd.), tetraisopropyl titanate (Shanghai McLean Biochemical Technology Co., Ltd.), hydrofluoric acid, methanol, ethanol, N,N-dimethylformamide (Chengdu Kelong Chemical Co., Ltd.).
[0020] Example 1 A method for preparing a photocatalytic-PMS activated catalyst based on Co-MOF / TiO2 heterojunction comprises the following steps: Step S1: 0.25 g of cobalt acetate tetrahydrate (1 mmol) was dissolved in 40 mL of methanol and sonicated for 10 min to form solution A; 0.13 g of porphyrin ligand (0.2 mmol) was dissolved in 40 mL of chloroform and sonicated for 10 min to form solution B; solution A and solution B were mixed, and the mixture was transferred to a 100 mL Teflon-lined stainless steel autoclave and reacted at 90 °C for 24 h; after naturally cooling to room temperature, the formed purple crystals were collected by centrifugation and washed with anhydrous ethanol 5 times to remove unreacted ligands and metal salts; the final washed product was vacuum dried at 60 °C for 12 h to obtain Co-MOF.
[0021] Step S2: Under continuous magnetic stirring, 6 mL of 40 wt% hydrofluoric acid was added dropwise to 50 mL of tetraisopropyl titanate. After stirring for 10 min, the mixture was transferred to a 100 mL Teflon-lined stainless steel autoclave and reacted at 190 °C for 24 h. After cooling naturally to room temperature, the gel-like white precipitate was collected by centrifugation and washed with anhydrous ethanol 5 times to remove the hydrofluoric acid in the system. The final washed product was vacuum dried at 60 °C for 12 h to obtain TiO2 nanosheets.
[0022] Step S3: Add 0.1 g of TiO2 nanosheets to 30 mL of DMF and sonicate for 1 h to form a uniform dispersion; then add 5 mg of Co-MOF to the solution and continue stirring for 12 h, where the mass of Co-MOF accounts for 5% of the total mass. Collect the precipitate by centrifugation, wash it with anhydrous ethanol 5 times, and dry it at 60 °C for 12 h to obtain the photocatalytic-PMS activated catalyst 1 based on the Co-MOF / TiO2 heterojunction.
[0023] Example 2 A method for preparing a photocatalytic-PMS activated catalyst based on Co-MOF / TiO2 heterojunction comprises the following steps: Step S1: same as step S1 in Example 1; Step S2: same as step S2 in Example 1; Step S3: Add 0.1 g of TiO2 nanosheets to 30 mL of DMF and sonicate for 1 h to form a uniform dispersion; then add 11 mg of Co-MOF to the solution and continue stirring for 12 h, where the mass of Co-MOF accounts for 10% of the total mass. Collect the precipitate by centrifugation, wash it with anhydrous ethanol 5 times, and dry it at 60 °C for 12 h to obtain the photocatalytic-PMS activated catalyst 2 based on the Co-MOF / TiO2 heterojunction.
[0024] Example 3 A method for preparing a photocatalytic-PMS activated catalyst based on Co-MOF / TiO2 heterojunction comprises the following steps: Step S1: same as step S1 in Example 1; Step S2: same as step S2 in Example 1; Step S3: Add 0.1 g of TiO2 nanosheets to 30 mL of DMF and sonicate for 1 h to form a uniform dispersion; then add 25 mg of Co-MOF to the solution and continue stirring for 12 h, where the mass of Co-MOF accounts for 20% of the total mass; collect the precipitate by centrifugation, wash it with anhydrous ethanol 5 times, and dry it at 60 °C for 12 h to obtain a photocatalytic-PMS activated catalyst 3 based on Co-MOF / TiO2 heterojunction.
[0025] Example 4 A method for preparing a photocatalytic-PMS activated catalyst based on Co-MOF / TiO2 heterojunction comprises the following steps: Step S1: same as step S1 in Example 1; Step S2: same as step S2 in Example 1; Step S3: Add 0.1 g of TiO2 nanosheets to 30 mL of DMF and sonicate for 1 h to form a uniform dispersion; then add 43 mg of Co-MOF to the solution and continue stirring for 12 h, where the mass of Co-MOF accounts for 30% of the total mass; collect the precipitate by centrifugation, wash it with anhydrous ethanol 5 times, and dry it at 60 °C for 12 h to obtain a photocatalytic-PMS activated catalyst 4 based on Co-MOF / TiO2 heterojunction.
[0026] Comparative Example 1: A method for preparing a Co-MOF photocatalyst comprises the following steps: 0.25 g of cobalt acetate tetrahydrate was dissolved in 40 mL of methanol and ultrasonicated for 10 min to form solution A; 0.13 g of porphyrin ligand was dissolved in 40 mL of chloroform and ultrasonicated for 10 min to form solution B; solution A and solution B were mixed, and the mixture was transferred to a 100 mL Teflon-lined stainless steel autoclave and reacted at 90 °C for 24 h. After cooling naturally to room temperature, the formed purple crystals were collected by centrifugation and washed with anhydrous ethanol 5 times to remove unreacted ligands and metal salts; the final washed product was vacuum dried at 60 °C for 12 h to obtain the Co-MOF photocatalyst.
[0027] Comparative Example 2: A method for preparing a TiO2 nanosheet photocatalyst comprises the following steps: Under continuous magnetic stirring, 6 mL of 40% hydrofluoric acid was added dropwise to 50 mL of tetraisopropyl titanate. After stirring for 10 min, the mixture was transferred to a 100 mL Teflon-lined stainless steel autoclave and reacted at 190 °C for 24 h. After naturally cooling to room temperature, the gel-like white precipitate formed was collected by centrifugation and washed five times with anhydrous ethanol to remove the hydrofluoric acid. The final washed product was vacuum dried at 60 °C for 12 h to obtain a TiO2 nanosheet photocatalyst.
[0028] Performance Test: 1. Photocatalytic performance: (1) Illumination / photocatalyst / PMS: The photocatalyst (20 mg) was placed in a reactor containing BPA solution (C0 = 20 mg / L, 100 mL), and then ultrasonicated for 2 min to fully disperse the catalyst. A 50W LED was used as the light source (λ>420 nm); the reactor was surrounded by a quartz sleeve filled with circulating cooling water; at the same time, 30 mg of PMS was injected to start the catalytic reaction; 2 mL of sample was immediately drawn with a syringe intermittently, and the test was quenched with 50 μL of Na2S2O3 solution (0.5 M), and then the suspended particles were separated by a 0.22 µm filter for subsequent analysis; the instantaneous concentration at different time points was monitored by UV-visible spectrometer to determine the change of BPA over time.
[0029] (2) Illumination: Omit the photocatalyst and PMS, and the rest is the same as (1); (3) PMS: omitting the photocatalyst and light source, the rest is the same as (1); (4) Light / PMS: Omit the photocatalyst, and the rest is the same as (1); (5) Photocatalyst / PMS: omitting the light source, the rest is the same as (1); (6) Light irradiation / photocatalyst: PMS is omitted, and the rest is the same as (1); 2. Cyclic performance: The photocatalyst (20 mg) in Example 3 was placed in a reaction solution containing BPA (100 mL, 10 mg / mL), and then ultrasonicated for 2 minutes to fully disperse the catalyst. Subsequently, 30 mg of PMS was added. During the reaction, 2 mL of the reaction solution was extracted every 5 minutes, and the supernatant was collected by centrifugation for the detection of BPA concentration. The detection method was the same as the photocatalytic performance test in the performance test. The solid obtained by centrifugation was redispersed in the reaction solution; after completing one cycle, the reaction solution was centrifuged to collect the catalyst, and washed with water three times, vacuum dried, and then the above steps were repeated.
[0030] Figure 1 The crystal structure of the prepared Co-MOF is Figure 1It can be seen that in Co-MOF, each Co ion is located at the center of the porphyrin, and the upper and lower adjacent porphyrin ligands are connected by coordination bonds to form a 3D metal-organic framework with a hexagonal pore structure.
[0031] Figure 2 The band structure of the catalysts prepared for Examples 1-4 and Comparative Examples 1-2 was studied. The optical properties of the catalysts were evaluated to assess their potential as photocatalysts; Figure 2 (a) shows the UV-vis DRS spectra of the catalysts; Comparative Example 2 (pure TiO2) has almost no absorption above 400 nm; compared with Comparative Example 2, the samples of Examples 1-4 show stronger light absorption ability, where the peaks at 429, 518, 552, 592 and 644 nm are related to the pp* transition between the lowest unoccupied molecular orbital and the highest occupied molecular orbital; the band gap value of the photocatalyst is derived according to the Kubelka-Munk theory ( Figure 2 (b)); the band gaps of Comparative Example 1, Comparative Example 2 and Examples 1-4 are 2.56, 3.22, 3.14, 3.06, 2.96 and 2.85 eV, respectively; it is worth noting that the introduction of Co-MOF will bring new impurity levels into the band gap, thereby reducing the band gap of the photocatalyst.
[0032] Figure 3 In order to explore the photocatalytic properties of the material through a series of comparative experiments; Figure 3 (a) The photocatalytic performance of the catalysts obtained in Comparative Examples 1-2 and Examples 1-4 on BPA under visible light was evaluated. The photocatalytic performance of the catalysts obtained in Comparative Examples 1-2 on BPA was limited; the performance of the catalysts obtained in Examples 1-4 was better than that of the single Comparative Examples 1 and 2; the degradation efficiency of the catalysts was improved with the increase of the Co-MOF content; the degradation rates of BPA by the catalysts obtained in Examples 1-4 within 60 min were 60.7%, 90.1%, 94.1% and 79.3%, respectively; this was attributed to the red shift of visible light absorption and the formation of heterojunction structures; among these composite materials, the photocatalytic performance of the catalyst obtained in Example 3 was the best; the pseudo-first-order (Formula (1)) and pseudo-second-order (Formula (2)) models were used in the photocatalytic kinetics study; (1) (2) Among them, C0 and C t represent the initial BPA concentration and the BPA concentration at t min, respectively; k1 and k2 represent the pseudo-first-order kinetic constant and the pseudo-second-order kinetic constant, respectively.
[0033] The BPA reduction rate of these samples conforms to the pseudo-first-order reaction kinetic model; the BPA removal rate conforms to the first-order reaction kinetics, and the apparent reaction kinetic constant of the catalyst obtained in Example 3 for degrading BPA is calculated to be 0.0444 min -1 , which is 7 and 57 times the reaction kinetic constants of Comparative Example 1 and Comparative Example 2 ( Figure 3 (b)).
[0034] Combined with the structural characteristics of Co-MOF, considering that Co-MOF may have PMS activation performance, the performance of degrading BPA under different conditions was tested, as shown in the following figure. Figure 3 (c), 3(d) and Table 1.
[0035] like Figure 3 As shown in (c), in the presence of visible light alone or PMS, the degradation rate of BPA in 60 min is less than 10%; in the visible light / PMS system, the degradation rate of BPA in 60 min is only 21.3%; in the presence of PMS, that is, the performance of Example 3 / PMS or illumination / Example 3 / PMS in degrading BPA is significantly greater than that of the illumination / Example 3 system, which means that Example 3 can activate PMS. On the other hand, the degradation performance of the illumination / Example 3 / PMS system is significantly greater than that of the Example 3 / PMS system. This shows that visible light also plays an important role in the process of activating the PMS system in Example 3. The removal rate of BPA conforms to the first-order reaction kinetics, and the apparent reaction kinetic constant for the degradation of BPA by the illumination / Example 3 / PMS system is calculated to be 0.0730min -1 , which is 1.6 times the reaction kinetic constant of the illumination / Example 3 and Example 3 / PMS systems ( Figure 3 (d)); The above results show that the catalyst obtained in Example 3 has both visible light catalytic performance and PMS activation performance, and has excellent performance in the process of degrading BPA.
[0036] Table 1 Comparison of the removal effects of the catalysts obtained in Example 3 on BPA under different conditions: condition Degradation rate (%) <![CDATA[Reaction rate constant (min -1 ).]]> illumination 0.185 0 PMS 11.259 0.0018 Light / PMS 21.344 0.0038 Example 3 / PMS 94.451 0.0464 Lighting / Example 3 94.041 0.0444 Lighting / Example 3 / PMS 99.709 0.0730 Figure 4 Real water contains a certain amount of coexisting ions; several inorganic anions (Cl - 、NO3 - 、CO3 2- 、HPO3 - 、HCO3 - and SO4 2- )( Figure 4(a)); The results showed that the inhibitory effect of all inorganic anions was minimal; compared with the control group, the addition of Cl - 、NO3 - and CO3 2- After 24h, the degradation rate of BPA remained almost unchanged; - Can be combined with SO4• - The reaction produces the less reactive •Cl and •Cl2 - Anion, NO3 - Can interact with electrons to form NO2 - SO4 2 - Slightly inhibits BPA degradation due to SO4 2- It will hinder the forward reaction in the activation of PMS, resulting in SO4 •- Reduce, degradation efficiency decreases; add HCO3 - and HPO4 2- It also inhibits the degradation of BPA. This is because HCO3 - and HPO4 2- Can react with •OH and SO4 •- react to form less reactive species (•HCO3, HPO4 •- ), thereby consuming •OH and SO4 •- , ultimately reducing BPA degradation. In addition, considering that there may be different reaction media in the actual application process, the effect of the light / Example 3 / PMS system on BPA degradation in different media was investigated; Figure 4 As shown in (b), there is no significant difference in the inhibitory effect of the illumination / Example 3 / PMS system on BPA in deionized water, tap water, lake water, river water and simulated seawater, which indicates that the catalyst has outstanding practical application potential.
[0037] Figure 5 The cyclic usability and stability test of the illumination / Example 3 / PMS system; Figure 5 As shown in (a), after five cycles, the illumination / Example 3 / PMS system can still maintain good BPA removal performance, and the removal rate remains above 90%, indicating that it has good reusability; in order to explore the stability of the catalyst structure before and after the reaction, the PXRD spectra of the catalyst obtained in Example 3 before and after the reaction were measured; the PXRD spectra of the catalyst obtained in Example 3 before and after the reaction ( Figure 5 (b)) is almost unchanged from before the reaction. These results indicate that the catalyst obtained in Example 3 has structural stability and anti-free radical capability in this specific system, which is also the basis for the catalyst obtained in Example 3 to be recycled.
[0038] Although the present invention has been disclosed as above in the form of a preferred embodiment, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.
[0039] The basic principles and main features of the present invention and the advantages of the present invention are shown and described above. For those skilled in the art, it is obvious that the present invention is not limited to the details of the above exemplary embodiments, and the present invention can be implemented in other specific forms without departing from the spirit or basic features of the present invention; therefore, no matter from which point of view, the embodiments should be regarded as exemplary and non-restrictive. The scope of the present invention is limited by the attached claims rather than the above description. Therefore, it is intended to include all changes within the meaning and scope of the equivalent elements of the claims in the present invention, and any figure marks in the claims should not be regarded as limiting the claims involved.
[0040] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A method for preparing a photocatalytic-PMS activated catalyst based on Co-MOF / TiO2 heterojunction, characterized in that: TiO2 nanosheets are added to DMF, ultrasonically dispersed evenly, and then Co-MOF is added, stirred for 6-18 hours, and the precipitate is collected by centrifugation, washed and dried to obtain a product in which Co-MOF accounts for 5-40% of the total mass of Co-MOF and TiO2 nanosheets.
2. The method for preparing the photocatalytic-PMS activated catalyst based on Co-MOF / TiO2 heterojunction according to claim 1, characterized in that: The concentration of cobalt acetate in solution A is 20-30 mmol / L, and the concentration of porphyrin ligand in solution B is 20-30 mmol / L.
3. A photocatalytic-PMS activated catalyst based on Co-MOF / TiO2 heterojunction prepared by the preparation method according to claim 1 or 2.
4. Use of the photocatalytic-PMS activated catalyst based on Co-MOF / TiO2 heterojunction as described in claim 3 in photocatalytic degradation of bisphenol A.
5. The use according to claim 4, characterized in that The Co-MOF / TiO2 heterojunction composite photocatalyst was added to a solution containing bisphenol A, a 50W LED lamp was used as the light source, and PMS was added under circulating water cooling to photocatalytically degrade bisphenol A.
6. The use according to claim 5, characterized in that The concentration of bisphenol A in the solution containing bisphenol A is 10-50 mg / L. Based on the solution containing bisphenol A, the added amount of Co-MOF / TiO2 heterojunction composite photocatalyst is 0.1-0.3 g / L, and the added amount of PMS is 0.2-0.4 g / L.
Citation Information
Patent Citations
TiO2-MOFs photocatalyst and preparation method and application thereof
CN108722497A
Preparation method of metalloporphyrin skeleton material sensitized titanium dioxide visible light response photocatalyst
CN109225331A
Preparation method of Co-MOF derived cobaltosic oxide composite titanium dioxide heterojunction and water electrolysis application
CN112619647A
Preparation method and application of B-TiO2-X-Co-TCPP composite material photocatalyst
CN115990519A
Porphyrinyl MOF / sulfur indium zinc heterojunction composite photocatalyst and preparation and application thereof
CN116440955A
Cited By
Catalytic material for activating persulfate based on light regulation, and preparation method and application thereof
CN121571174A
Photo-activated persulfate catalytic materials, their preparation methods, and applications.
CN121571174B